2015
DOI: 10.4103/0366-6999.164927
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of Sodium Hyaluronate on Ocular Surface Damage Induced by Benzalkonium Chloride Preserved Anti-glaucoma Medications

Abstract: Background:Long-term use of benzalkonium chloride (BAC)-preserved drugs is often associated with ocular surface toxicity. Ocular surface symptoms had a substantial impact on the glaucoma patients’ quality of life and compliance. This study aimed to investigate the effects of sodium hyaluronate (SH) on ocular surface toxicity induced by BAC-preserved anti-glaucoma medications treatment.Methods:Fifty-eight patients (101 eyes), who received topical BAC-preserved anti-glaucoma medications treatment and met the sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 36 publications
0
16
0
1
Order By: Relevance
“…In a trial comparing safety and efficacy of hydroxypropyl-methycellulose/dextran with 0.18% sodium hyaluronate, glaucoma patients with ocular surface disease who used 0.18% sodium hyaluronate showed significantly more improvement in mean OSDI score, lid margin inflammation, and conjunctival injection 81 . For patients who are tolerant to BAK preserved anti-glaucoma medications, adding sodium hyaluronate containing artificial tears as an adjunct appears to decrease OSDI scores, increase goblet cell density, and increase TBUT 8284 . Furthermore, visual field test parameters were improved in patients using artificial tears, highlighting the impact of a stable tear film and healthy corneal surface 1 .…”
Section: Management Of Ocular Surface Disease In Conjunction With Glamentioning
confidence: 99%
“…In a trial comparing safety and efficacy of hydroxypropyl-methycellulose/dextran with 0.18% sodium hyaluronate, glaucoma patients with ocular surface disease who used 0.18% sodium hyaluronate showed significantly more improvement in mean OSDI score, lid margin inflammation, and conjunctival injection 81 . For patients who are tolerant to BAK preserved anti-glaucoma medications, adding sodium hyaluronate containing artificial tears as an adjunct appears to decrease OSDI scores, increase goblet cell density, and increase TBUT 8284 . Furthermore, visual field test parameters were improved in patients using artificial tears, highlighting the impact of a stable tear film and healthy corneal surface 1 .…”
Section: Management Of Ocular Surface Disease In Conjunction With Glamentioning
confidence: 99%
“…This is a novel option to transport active pharmaceutical ingredients (API) with HMW HA molecules as vehicle through the cell membrane of epithelial cells without damaging the cell membrane. In combination with the ability of HA to ameliorate the negative effects of corneotoxic substances [93,[255][256][257], it is anticipated that particularly patients requiring long-term topical treatment of diseases like glaucoma, who currently suffer from negative side effects of their treatment, will benefit from the new technology.…”
Section: Discussionmentioning
confidence: 99%
“…The use of hyaluronan in ophthalmic drug vehicles has been suggested in numerous publications [242,[248][249][250][251][252][253][254]. Hyaluronan has a proven effect of counteracting the irritating effect of substances to the ocular epithelium [93,[255][256][257].…”
Section: Hyaluronan Eye Drops As a Vehicle For Active Pharmaceutical mentioning
confidence: 99%
“…For example, in 1986 Wittpenn et al [19] first demonstrated reduced goblet cell numbers and increased epithelial cell size of the conjunctiva in vitamin A deficiency-induced xerophthalmia in children, and suggested a role for IC in early detection of this condition. Since then, various groups have used IC to assess the effects of DED therapies on the ocular surface, including the effects of preservatives in ophthalmic medications and autologous serum [20][21][22]. A summary of potential OSD-related biomarkers using IC can be found in Table 1.…”
Section: Impression Cytology and Ocular Surface Diseasementioning
confidence: 99%